Enzymatic tandem systems engineered from mesoporous thin films: Synergy leading to efficient starch-electricity conversion - Bellino, Martin Gonzalo; Municoy, Sofia; Soler Illia, Galo Juan de Avila Arturo (Elsevier, 2016)
Fil: Bellino, Martin Gonzalo. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Comisión Nacional de Energía Atómica. Centro Atómico Constituyentes; Argentina